2014
DOI: 10.1007/s13659-014-0028-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traditional Chinese Medicinal Plants on Anti-insulin Resistance Bioactivity of DXMS-Induced Insulin Resistant HepG2 Cells

Abstract: Medicinal plants have a long history of use in China to treat diabetic symptoms. Ancient Chinese medical manuscripts and ethnobotanical surveys document plant remedies that continue to be actively used in China for the treatment of diabetic symptoms. Based on a systematic ancient Chinese medical manuscripts review in combination with ethnobotanical survey, 16 medicinal plants for the traditional treatment of diabetic symptoms were identified for the evaluation of anti-insulin resistance bioactivity. The biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
1
2
1
Order By: Relevance
“…The effects of QJJ on HepG2 cell viability and glucose uptake suggest that it can attenuate the apoptosis and necrosis of HepG2 cells and increase the glucose uptake, exerting protective effect on IR. This is in contrast to a study by Ma et al [ 30 ] in which Astragalus membranaceus was ineffective at increasing insulin sensitivity of dexamethasone-induced insulin resistant HepG2 cells. The inconsistencies may be due to the in vitro IR model employed as APS improved glucose uptake by C2C12 skeletal muscle myotubes after induction of palmitate-induced IR [ 31 ], and Rehmannia increased glucose uptake by insulin resistant HepG2 cells [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The effects of QJJ on HepG2 cell viability and glucose uptake suggest that it can attenuate the apoptosis and necrosis of HepG2 cells and increase the glucose uptake, exerting protective effect on IR. This is in contrast to a study by Ma et al [ 30 ] in which Astragalus membranaceus was ineffective at increasing insulin sensitivity of dexamethasone-induced insulin resistant HepG2 cells. The inconsistencies may be due to the in vitro IR model employed as APS improved glucose uptake by C2C12 skeletal muscle myotubes after induction of palmitate-induced IR [ 31 ], and Rehmannia increased glucose uptake by insulin resistant HepG2 cells [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This makes them an ideal cell model for studying IR. [43][44][45] This study, which is consistent with previous studies, revealed that PA reduced uptake of a glucose molecule and glycogen synthesis in HepG2 cells to a significant extent, indicating that the cell model of IR was successfully established. 4,7) QAG, a flavonoid isolated from EUOL, increased uptake of glucose as well as glycogen synthesis in PA-induced HepG2cells, thus improving IR.…”
Section: Discussionsupporting
confidence: 91%
“…There are many methods for establishing an insulin resistance model in hepatocytes in vitro, such as high glucose induction,8 insulin induction,9 high glucose combined with insulin induction,10 PA induction,11 and dexamethasone induction 12. Here, we used 0.25 mmol/L PA treatment, which is the concentration chosen in most studies5 and in our previous study.…”
Section: Discussionmentioning
confidence: 99%